Regional issues on firm entry and exit in Argentina: core and peripheral regions - Calá, Carla Daniela (2014)
This work focuses on two fundamental and relevant questions: a) are there any differences in the regional determinants of entry and exit between developed and developing economies?; b) are there any differences in the regional determinants of entry and exit between core and peripheral regions within a single country? To address these issues, we take as a starting point a set of determinants that are generally found to be statistically significant in regional entry and exit studies using data from developed countries (e.g., demand, education, density and industrial structure). Then, we add some factors that, while potentially important in developing countries, are never considered by studies on developed countries. This is the case, for example, of the size of the informal economy, the extent of poverty or the usage of idle capacity after an economic crisis. Finally, we explore the existing of a core-periphery pattern, that is, we test whether the same factors affect entry and exit in a similar way in central and peripheral provinces.